Pengembangan Usahatani Cabai Merah di Lahan Pasir Pantai Kecamatan Temon Kabupaten Kulonprogo - Eni Istiyanti; Uswatun Khasanah; Arifah Anjarwati (Universitas Muhammadiyah Yogyakarta, 2015)
The objective of this research is determine the profit of red chili farming coastal land, the factors that influence of red chili production and efficiency used of production factors on red chili farming on coastal land in Temon subdistrict Kulon Progo Regency. Selection of the location is used purposive method.Fourty farmer sampling were taken as simple random sampling. The analysis method is used Multiple Regression Analysis with Ordinary Least Square (OLS) method. The result showed that the income of red chili farming in coastal land is Rp 9.278.430/0,38 ha and the profit is Rp 3.094.504/0,38 ha. The production factors concists of the soil of area, number of seeds, amount of labors, manure fertilizer, dunk fertilizer, Za chemic fertilizer, SP 36 fertilizer, NPK Mutiara fertilizer, Phonska fertilizer, Furadan insecticide, Ampligo fungicide, Anthracol fungicide, Confidor insecticide, the kind of seeds and used of mulch aggregated influences to red chili production. The production factors number of seeds, amount of labors, manure fertilizer, NPK Mutiara fertilizer, Ampligo fungicide, kind of seeds and used mulch partially influences to red chili production on coastal land. Seed applied on red chili farming on coastal land is efficient.